2003
DOI: 10.1097/00001756-200308060-00009
|View full text |Cite
|
Sign up to set email alerts
|

A new electrophysiological index for working memory load in humans

Abstract: Working memory, the ability to store and simultaneously manipulate information, is affected in several neuropsychiatric disorders which lead to severe cognitive and functional deficits. An electrophysiological marker for this process could help identify early cerebral function abnormalities. In subjects performing working memory-specific n-back tasks, event-related potential analysis revealed a positive-negative waveform (PNwm) component modulated in amplitude by working memory load. It occurs in the expected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…Among the neuronal responses reflecting these processes a reliable effect of attention on P2 amplitude was previously reported (Missonnier et al, 2003). Given that mental workload is inversely related to attentional reserve, Miller et al (2011) suggested that the P2 amplitude decrease may represent a reduction in the allocation of attention to the target stimuli.…”
Section: Discussionmentioning
confidence: 91%
“…Among the neuronal responses reflecting these processes a reliable effect of attention on P2 amplitude was previously reported (Missonnier et al, 2003). Given that mental workload is inversely related to attentional reserve, Miller et al (2011) suggested that the P2 amplitude decrease may represent a reduction in the allocation of attention to the target stimuli.…”
Section: Discussionmentioning
confidence: 91%
“…In particular, a significant decrease of P200 and N200 latencies is observed after stimulus onset during the 2 working memory conditions. 14,15 This decrease may correspond to the encoding and retrieval phases of working memory processing that follow sensory processes. 16,17 Among brain oscillations, earlier reports pointed to the reactivity of the θ frequency bands (4-8 Hz) to various memory paradigms reflecting the corticohippocampal interactions needed in case of increasing memory load.…”
Section: Introductionmentioning
confidence: 99%
“…Two earlier studies revealed that modulation of P200 and N200 latencies during the n-back task is related to the development of an additional working memory load-related parietal compon ent. 14,15 To our knowledge, this study is the first to explore P200 and N200 latencies in patients with first-episode psychosis using working memory paradigms. As expected, P200 latencies decreased as a function of working memory load in patients and controls.…”
mentioning
confidence: 96%
“…Short lasting b-oscillations have been observed following voluntary hand movement (Pfurtscheller et al, 1997;Lalo et al, 2007) whereas lower frequency oscillations such as, d (1-3 Hz) have been linked with sleep. By contrast, cortical oscillations in the g (30-50 Hz) band frequency recorded from the dorsolateral prefrontal cortex (DLPFC) and the hippocampus represent important electrophysiological processes, which have been associated with higher order cognitive tasks including working memory (TallonBaudry and Bertrand, 1999;Howard et al, 2003;Kaiser and Lutzenberger, 2003;Missonnier et al, 2003). For example, increases in working memory loads have been associated with increases in the power of induced g-oscillations in the DLPFC of healthy human subjects (Howard et al, 2003) and abnormalities of g-oscillations have been associated with the working memory deficits in patients with schizophrenia (Cho et al, 2006).…”
Section: Introductionmentioning
confidence: 99%